Migration of amphibians and their Mortality on the road of Knyszyn forest landscape park - Maciej Arciszewski (Acta Biologica, 2015)
Spring migration and mortality of two common amphibian species on the road in one of the landscape parks in north-eastern Poland (Knyszyn Forest Landscpae Park) were studied in the years 2013–2015. During three years of the study, total number of 2745 individuals classified to 7 different species and one amphibian group were transfered through the road. The most popular species caught into the traps were: common toad, smooth newt and the common frog. Mortality of two studied amphibian species (Bufo bufoand rana temporaria) dropped over three years of the study. There were positive significant correlation between temperature and the number of migrating amphibians on the road.